2011
DOI: 10.1128/aac.00173-11
|View full text |Cite
|
Sign up to set email alerts
|

Applying New Diagnostic Criteria for Acute Kidney Injury To Facilitate Early Identification of Nephrotoxicity in Vancomycin-Treated Patients

Abstract: Acute kidney injury (AKI) associated with high-dose vancomycin (VAN) therapy is a clinical concern, but no uniform diagnostic criteria exist. The AKI Network (AKIN) proposed new criteria to diagnose AKI based on abrupt changes in serum creatinine or urine output. We conducted a prospective observational study to determine the incidence and severity of AKI and associated outcomes using the AKIN criteria versus traditional definitions. Eligible patients (n ‫؍‬ 227) were elderly (median, 70 years) and received VA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(142 citation statements)
references
References 14 publications
7
130
3
2
Order By: Relevance
“…All of these variables were previously reported in the literature (2,14,15). Receipt of any concomitant nephrotoxin, vasopressors, or aminoglycosides or of an increasing number of nephrotoxins has been associated with nephrotoxicity (2,(16)(17)(18)(19). In our study, 68% of patients received at least one concomitant nephrotoxin; however, the association with increased odds of nephrotoxicity remained significant only if patients received at least two concomitant nephrotoxins.…”
Section: Discussioncontrasting
confidence: 34%
“…All of these variables were previously reported in the literature (2,14,15). Receipt of any concomitant nephrotoxin, vasopressors, or aminoglycosides or of an increasing number of nephrotoxins has been associated with nephrotoxicity (2,(16)(17)(18)(19). In our study, 68% of patients received at least one concomitant nephrotoxin; however, the association with increased odds of nephrotoxicity remained significant only if patients received at least two concomitant nephrotoxins.…”
Section: Discussioncontrasting
confidence: 34%
“…Of these, 14 studies were conducted with adults and 1 involved children (38) ( Table 1). The average trough value over the duration of therapy was examined in 6 studies (13,30,38,39,43,50), and the initial trough value was considered in 8 studies (8, 15, 21-23, 32, 36, 51). Although timing differed between studies, most initial trough levels were obtained at the time or shortly after steady state was achieved (i.e., after the 3rd dose) but not greater than 4 days into therapy (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Minejima et al (21) showed that the AKIN criteria were more sensitive than traditional criteria in detecting vancomycin nephrotoxicity. In their opinion, early detection of vancomycin nephrotoxicity has the potential to improve management because it may lead to changes in management that halt the process of renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…AKI was defined and staged according to RIFLE (18), AKIN (19), and KDIGO (20) criteria. For comparison, we also defined AKI using two traditional nephrotoxicity (NT) criteria (21). Since we did not have access to urinary output data, AKI diagnoses were based solely on the magnitude of the increases in SCr levels (Fig.…”
Section: Methodsmentioning
confidence: 99%